FOOD PRACTICES OF SCHOOL TEENS ATTENDED IN A PHILANTHROPIC INSTITUTION WITH REFERENCE TO HEARING IMPAIRED IN MACAÉ, RIO DE JANEIRO. (Fiep Bulletin - online, 2014)
The study aims to describe the dietary patterns of hearing impaired children and adolescents attended at an institution in the Lakes Region and North Fluminense, Rio de Janeiro. It is a cross-sectional study, conducted at Associação Macaense do Deficiente Auditivo, from April 2010-12. Graduates interviewed children and adolescents between 07 to 19.9 years old, with help from a sign-language interpreter and/or family members. The evaluated variables: gender, age, number of meals per day, food allergies, food aversions, if they joined their family buying food and preparing their own food. Everybody gave their informed consent signed by parents. Information was analyzed from 28 children and adolescents, 60.9% male and 39.1% female, with an average (± SD) age of 12.6 ± 3.08 years old. As for the number of meals per day, 64.3% held 3-4 meals and 35.7% performed above 4. About 40% reported having some type of food aversion. 32% of respondents reported that they accompany the family on purchases of food and 36% reported that they prepare their own food, in particular snacks. It was perceived that the group had low intake of vegetables, about one third accompany the family shopping and prepare their own food, especially snacks, probably due to its practicality.
Keywords: Deafness; Hearing Loss; Food Consumption